Compositional and crystallographic design of Ni-Co phosphide heterointerfaced nanowires for high-rate, stable hydrogen generation at industry-relevant electrolysis current densities. (May 2022) - Ma, Shunfeng; Qu, Xianlin; Huang, Jun; Zhang, Cheng; Chen, Guangliang; Chen, Wei; Li, Tongtong; Shao, Tao; Zheng, Kun; Tian, Jietao; Li, Chaorong; Ostrikov, Kostya (Ken)
Abstract: Lack of high-performance noble-metal free electrocatalysts for hydrogen evolution reaction (HER) to exceed the benchmark Pt-based electrocatalysts, still remains a major hurdle on the way to clean hydrogen economy. Here we rationally, atomistically design and synthesize the hetero-interfaced Ni-Co phosphide nanowires which deliver exceptional activity and stability in water electrolysis under industry-relevant current densities. The compositional and crystallographic design produces extra-stable Ni5 P4 -Co2 P nanowires sprouting from a Ni-Co alloy foam (NCF). The extraordinary reactivity is ensured by the heterointerfaces between the highly-active (303) crystal planes of Co2 P and Ni5 P4 nanowire phases. The overpotentials of Ni5 P4 -Co2 P/NCF catalysts at −10, −100, and −1000 mA cm −2 are about 21, 92 and 267 mV in 1 M KOH, respectively, far exceeding the commercial Pt/C catalysts. The Tafel slope of Ni5 P4 -Co2 P/NCF catalyst is only 23 mV dec −1, indicating an even faster HER kinetic compared to Pt/C (32 mV dec −1 ). Moreover, the Ni5 P4 -Co2 P/NCF catalyst shows an ultra-stable and lasting performance, evidenced by only a minor 3.6% drop at j 250 after 100 h continuing operation. The DFT calculations confirm that the exposed heterointerfaces between (303) planes of Ni5 P4 and Co2 P phases play a key role for boosting the HER activity of Ni5 P4 -Co2 P electrocatalyst. Graphical Abstract: Rational atomistic design and synthesis of Ni-Co phosphide heterointerfaced nanowire electrocatalysts are demonstrated. The achieved high-rate, stable hydrogen generation at industry-relevant current densities are highlighted by the very low overpotentials of 21 and 267 mV at the current density of 10 and 1000 mA cm −2, respectively, and the highest-reported H2 generation rate (2.4 mmol·h −1 ). ga1 Highlights: Ni5 P4 -Co2 P nanowire array directly sprouted from NiCo foam with one-step CVD method. Rich heterointerfaces are obtained in the Ni5 P4 -Co2 P nanowire. In-situ engineering the high-active crystal plane of (303) in nanosized catalyst. HER performance of Ni5 P4 -Co2 P nanowire overwhelms that of benchmark Pt. High electrocatalytic activity and superior stability for HER with a full pH range.